Utilisation of the OliveNet™ Library to investigate phenolic compounds using molecular modelling studies in the context of Alzheimer's disease. (August 2020) - Liang, Julia; Pitsillou, Eleni; Man, Abella Y.L.; Madzima, Sibonginkosi; Bresnehan, Sarah M.; Nakai, Michael E.; Hung, Andrew; Karagiannis, Tom C.
Graphical abstract: Highlights: The phenolics from the OliveNet™ Library were utilised in molecular modelling studies of Alzheimer's disease. Molecular docking studies were performed against the major pathogenic proteins, β-amyloid (Aβ) and tau. Key binding sites were identified using molecular docking, highlighting the hairpin-turn of the Aβ1−40 and Aβ1−42 peptides. The flavonoid, glucoside and secoiridoid subclasses were found to bind with highest affinity to the pathogenic proteins. Dynamic simulations depicted can be used to investigate anti-aggregatory effects of compounds from the OliveNet™ Library. Abstract: Alzheimer's disease (AD) is a debilitating neurodegenerative disease that affects over 47 million people worldwide, and is the most common form of dementia. There is a vast body of literature demonstrating that the disease is caused by an accumulation of toxic extracellular amyloid-β (Aβ) peptides and intracellular neurofibrillary tangles that consist of hyperphosphorylated tau. Adherence to the Mediterranean diet has been shown to reduce the incidence of AD and the phenolic compounds in extra virgin olive oil, including oleocanthal, have gained a significant amount of attention. A large number of these ligands have been described in the pre-existing literature and 222 of these compounds have been characterised in the OliveNet™ database. In this study, molecular docking was used to screen the 222 phenolic compounds from the OliveNet™ database and assess their ability to bind to various forms of the Aβ and tau proteins. The phenolic ligands were found to be binding strongly to the hairpin-turn of the Aβ1−40 and Aβ1−42 monomers, and binding sites were also identified in the tau fibril protein structures. Luteolin-4′- O -rutinoside, oleuricine A, isorhoifolin, luteolin-7- O -rutinoside, cyanidin-3- O -rutinoside and luteolin-7, 4- O -diglucoside were predicted to be novel lead compounds. Molecular dynamics (MD) simulations performed using well-known olive ligands bound to Aβ1−42 oligomers highlighted that future work may examine potential anti-aggregating properties of novel compounds in the OliveNet™ database. This may lead to the development and evaluation of new compounds that may have efficacy against Alzheimer's disease.